2020
DOI: 10.1002/chem.201905552
|View full text |Cite
|
Sign up to set email alerts
|

Filling a Gap: The Coordinatively Saturated Group 4 Carbonyl Complexes TM(CO)8 (TM=Zr, Hf) and Ti(CO)7

Abstract: Homoleptic Group 4 metal carbonyl cation and neutral complexes were prepared in the gas phase and/or in solid neon matrix. Infrared spectroscopy studies reveal that both zirconium and hafnium form eight‐coordinate carbonyl neutral and cation complexes. In contrast, titanium forms only the six‐coordinate Ti(CO)6+ and seven‐coordinate Ti(CO)7. Titanium octacarbonyl Ti(CO)8 is unstable as a result of steric repulsion between the CO ligands. The 20‐electron Zr(CO)8 and Hf(CO)8 complexes represent the first experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 77 publications
2
31
0
Order By: Relevance
“…[38][39][40] For Ti(N 2 ) 8 ,t he cubic singlet structure is only al ocal minimum, which is thermodynamically unstable for loss of one N 2 ligand leading to Ti(N 2 ) 7 as the coordinatively saturated stable complex, similar to the octa-coordinated CO complexes. [9] The M VI (N 2 ) 6 complexes are also singlet species. All neutral complexes have O h symmetry in their ground state, and all geometry optimizations were performed using the M06-2X-D3 functional and the def2-TZVPPb asis set for all atoms using the Gaussian [41] software conforming with recent work on octa-coordinated alkaline earth complexes.…”
Section: Electronicstructure Of the M(l) 8 And M(l) 6 Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[38][39][40] For Ti(N 2 ) 8 ,t he cubic singlet structure is only al ocal minimum, which is thermodynamically unstable for loss of one N 2 ligand leading to Ti(N 2 ) 7 as the coordinatively saturated stable complex, similar to the octa-coordinated CO complexes. [9] The M VI (N 2 ) 6 complexes are also singlet species. All neutral complexes have O h symmetry in their ground state, and all geometry optimizations were performed using the M06-2X-D3 functional and the def2-TZVPPb asis set for all atoms using the Gaussian [41] software conforming with recent work on octa-coordinated alkaline earth complexes.…”
Section: Electronicstructure Of the M(l) 8 And M(l) 6 Complexesmentioning
confidence: 99%
“…The synthesis and characterization as cubic octa-carbonyl complexes of both the anionic group III complexesa nd the neutral group IV complexes was also recently reported by the same authors. [8,9] In the abovementioned heavy alkaline earth main-groupm etal complexes, the metal-CO bondingw as scrutinized, and was shown to be dominated by the M(dp)! (CO) 8 p back-donation of the degenerate (e g ) set of singly occupied( nÀ1)d atomico rbitals of the metal into the antibonding p*m olecular orbitals (MOs) of CO. [8] Further analysiss hows that the complexes obey the 18-electronr ule if only those electrons are countedt hat are engaged in the metal-ligand interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 The recent work on the first observation of coordinatively saturated carbonyl complexes of group 4 reported the surprising finding of octacarbonyls M(CO) 8 for M = Zr, Hf instead of heptacarbonyls. 36 In the case of Ti only the heptacarbonyl Ti(CO) 7 was observed. Note that stable salts of the isoelectronic cations [M’(CO) 7 ] + (M’ = Nb, Ta) were recently synthesized.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Theoretical calculations showed that the coordinatively saturated Ti(CO) 8 is a minimum on the potential energy surface, but it is thermodynamically unstable for the loss of one CO. 36 This is likely due to the release of interligand repulsion in the titanium octacarbonyl, which has significantly shorter metal–CO bonds than the heavier group 4 homologues. 36 The analysis of the electronic structure of the octacarbonyls M(CO) 8 , which are formally 20-electron species, showed that one (a 2u ) occupied valence orbital of the complexes having cubic ( O h ) symmetry has only coefficients at the CO ligands. The s/p/d valence AOs of the metals do not have proper symmetry to mix with the a 2u MO of (CO) 8 ( O h ).…”
Section: Introductionmentioning
confidence: 99%